Determinants of post-COVID-19 symptoms among adults aged 55 or above with chronic conditions in primary care: data from a prospective cohort in Hong Kong - Zhang, Dexing; Chung, Vincent Chi-Ho; Chan, Dicken Cheong-Chun; Xu, Zijun; Zhou, Weiju; Tam, King Wa; Lee, Rym Chung-Man; Sit, Regina Wing-Shan; Mercer, Stewart W.; Wong, Samuel Yeung-Shan (Frontiers in Public Health, 2023)
Background Primary care patients, especially those with an older age, are one of the most vulnerable populations for post-COVID-19 symptoms. Identifying predictors of post-COVID symptoms can help identify high-risk individuals for preventive care. Methods Out of 977 primary care patients aged 55 years or above with comorbid physical and psychosocial conditions in a prospective cohort in Hong Kong, 207 patients infected in the previous 5–24 weeks were included. The three most common post-COVID-19 symptoms (breathlessness, fatigue, cognitive difficulty), which lasted beyond the 4-week acute infection period, were assessed using items from the COVID-19 Yorkshire Rehabilitation Scale (C19-YRS), together with other self-reported symptoms. Multivariable analyses were conducted to identify predictors of post-acute and long COVID-19 symptoms (5–24 weeks after infection). Results The 207 participants had a mean age of 70.8 ± 5.7 years, 76.3% were female, and 78.7% had ≥2 chronic conditions. In total, 81.2% reported at least one post-COVID symptom (mean: 1.9 ± 1.3); 60.9, 56.5 and 30.0% reported fatigue, cognitive difficulty, and breathlessness respectively; 46.1% reported at least one other new symptom (such as other respiratory-related symptoms (14.0%), insomnia or poor sleep quality (14.0%), and ear/nose/throat symptoms (e.g., sore throat) (10.1%), etc.). Depression predicted post-COVID-19 fatigue. The female sex predicted cognitive difficulty. Receiving fewer vaccine doses (2 doses vs. 3 doses) was associated with breathlessness. Anxiety predicted a higher overall symptom severity level of the three common symptoms. Conclusion Depression, the female sex, and fewer vaccine doses predicted post-COVID symptoms. Promoting vaccination and providing intervention to those at high-risk for post-COVID symptoms are warranted.